An anti-inflammatory eicosanoid switch mediates the suppression of type-2 inflammation by helminth larval products - de los Reyes Jiménez, Marta; Lechner, Antonie; Alessandrini, Francesca; Bohnacker, Sina; Schindela, Sonja; Trompette, Aurélien; Haimerl, Pascal; Thomas, Dominique; Henkel, Fiona; Mourão, André; Geerlof, Arie; da Costa, Clarissa Prazeres; et al. (Science Translational Medicine, 2020)
Eicosanoids are key mediators of type-2 inflammation, e.g., in allergy and asthma. Helminth products have been suggested as remedies against inflammatory diseases, but their effects on eicosanoids are unknown. Here, we show that larval products of the helminth Heligmosomoides polygyrus bakeri (HpbE), known to modulate type-2 responses, trigger a broad anti-inflammatory eicosanoid shift by suppressing the 5-lipoxygenase pathway, but inducing the cyclooxygenase (COX) pathway. In human macrophages and granulocytes, the HpbE-driven induction of the COX pathway resulted in the production of anti-inflammatory mediators [e.g., prostaglandin E2 (PGE2) and IL-10] and suppressed chemotaxis. HpbE also abrogated the chemotaxis of granulocytes from patients suffering from aspirin-exacerbated respiratory disease (AERD), a severe type-2 inflammatory condition. Intranasal treatment with HpbE extract attenuated allergic airway inflammation in mice, and intranasal transfer of HpbE-conditioned macrophages led to reduced airway eosinophilia in a COX/PGE2-dependent fashion. The induction of regulatory mediators in macrophages depended on p38 mitogen-activated protein kinase (MAPK), hypoxia-inducible factor-1α (HIF-1α), and Hpb glutamate dehydrogenase (GDH), which we identify as a major immunoregulatory protein in HpbE. Hpb GDH activity was required for anti-inflammatory effects of HpbE in macrophages, and local administration of recombinant Hpb GDH to the airways abrogated allergic airway inflammation in mice. Thus, a metabolic enzyme present in helminth larvae can suppress type-2 inflammation by inducing an anti-inflammatory eicosanoid switch, which has important implications for the therapy of allergy and asthma.
CRIS-Team Scopus Importer:2020-05-05